2014
DOI: 10.4314/tjpr.v13i9.4
|View full text |Cite
|
Sign up to set email alerts
|

<i>In vivo</i> Evaluation of a Cosmetic Emulsion Containing Soybean Extract for Anti-Aging

Abstract: SEw (skin wrinkles, from 71.74 ± 1.52 to 68.51 ± 1.64), SEsm (skin smoothness, from 109.01 ± 4.77 to 102.03 ± 4.23), and SEr (skin roughness, from 4.04 ± 0.09 to 3.82 ± 0.08)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 16 publications
(17 reference statements)
0
9
0
Order By: Relevance
“…Increased wrinkling, decreased elasticity, uneven pigmentation, and increased roughness and dryness are common signs of skin aging (1,2). Plants with natural antioxidant components that possess antiaging activities may have cosmetic applications.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Increased wrinkling, decreased elasticity, uneven pigmentation, and increased roughness and dryness are common signs of skin aging (1,2). Plants with natural antioxidant components that possess antiaging activities may have cosmetic applications.…”
Section: Discussionmentioning
confidence: 99%
“…UV radiation activates elastase secretion via ROS formation, resulting in a decreased elastin content, leading to wrinkles (2,3,33). The inhibition of skin elastase and tyrosinase serves a key role in the antiwrinkle and skin-evening activities (4,7,33).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Waqas et al [70] used an elastometer to confirm the anti-ageing and elasticity-inducing effect on the skin following treatment with a cosmetic formulation containing soybean extract. Lee et al [71] suggested curcumin as a potential cosmetic ingredient after observing that it increases the expression of tropoelastin in human dermal fibroblasts.…”
Section: Cosmetics and Photoageingmentioning
confidence: 99%